2011
DOI: 10.1016/j.brainresrev.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of the central noradrenergic system in behavioral inhibition

Abstract: Although the central noradrenergic system has been shown to be involved in a number of behavioral and neurophysiological processes, the relation of these to its role in depressive illness has been difficult to define. The present review discusses the hypothesis that one of its chief functions that may be related to affective illness is the inhibition of behavioral activation, a prominent symptom of the disorder. This hypothesis is found to be consistent with most previous neuropsychopharmacological and immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 180 publications
(230 reference statements)
0
24
0
2
Order By: Relevance
“…This indicates that depression might increase the risk of morbidity among evening types. Noradrenergic transmission has been implicated as dysfunctional in depressed individuals (Checkley, 1980;Stone et al, 2011) and may underlie some of the associations we found herein such as a faster resting heart rate. However, because we did not assess any direct indicators of this transmission pathway, it remains speculative.…”
Section: Discussionmentioning
confidence: 60%
“…This indicates that depression might increase the risk of morbidity among evening types. Noradrenergic transmission has been implicated as dysfunctional in depressed individuals (Checkley, 1980;Stone et al, 2011) and may underlie some of the associations we found herein such as a faster resting heart rate. However, because we did not assess any direct indicators of this transmission pathway, it remains speculative.…”
Section: Discussionmentioning
confidence: 60%
“…Most intriguingly, symptoms of anhedonia and inhibition have also been suggested to be a consequence of noradrenergic hyperactivity [78,79] . Furthermore, the tonic hyperarousal explains the pronounced insomnia in depression, including the increased sleep onset latency [80,81] .…”
Section: The Vigilance Regulation Model Of Affective Disorders and Adhdmentioning
confidence: 99%
“…However, the functional meaning of this phenomenon remains unclear. Some researchers suggest overinhibition of LC neuron activity mediated by  2 -AR, which is attenuated by antidepressant treatment that targets this receptor (Cottingham and Wang, 2012); other researchers claim the contrary that the increased activity of the LC neurons may contribute to a depressive state (Stone et al, 2011). The latter hypothesis is supported by previous experiments that demonstrated the administration of  2 -AR agonists or antagonists into the LC region induces an antidepressant effect or depressive-like behavior, respectively, in the forced swimming test (FST) (Weiss et al, 1986).…”
Section: Accepted Manuscriptmentioning
confidence: 97%